Occurrence of liver cirrhosis in England, a cohort study, 1998-2009: a comparison with cancer - Ratib, Sonia; West, Joe; Crooks, Colin J.; Fleming, Kate M. (Nature Publishing Group, 2014)
OBJECTIVES: There is no routine registration of the occurrence of newly diagnosed cases of cirrhosis in the United Kingdom. This study seeks to determine precise estimates and trends of the incidence of cirrhosis in England, and directly compare these figures with those for the 20 most commonly diagnosed cancers in the United Kingdom. METHODS: We used the Clinical Practice Research Datalink and linked English Hospital Episode Statistics to perform a population-based cohort study. Adult incident cases with a diagnosis of cirrhosis between January 1998 and December 2009 were identified. We described trends in incidence by sex and etiology. We performed a direct standardization to estimate the number of people being newly diagnosed with cirrhosis in 2009, and calculated the change in incidence between 1998 and 2009. RESULTS: A total of 5,118 incident cases of cirrhosis were identified, 57.9% were male. Over the 12-year period, crude incidence increased by 50.6%. Incidence increased for both men and women and all etiology types. We estimated approximately 17,000 people were newly diagnosed with cirrhosis in 2009 in the United Kingdom, greater than that of the fifth most common cancer non-Hodgkin's lymphoma. The percentage change in incidence of cirrhosis between 1998 and 2009 for both men (52.4%) and women (38.3%) was greater than that seen for the top four most commonly diagnosed cancers in the United Kingdom (breast, lung, bowel, and prostate). CONCLUSIONS: The occurrence of cirrhosis increased more than that of the top four cancers during 1998 to 2009 in England. Strategies to monitor and reduce the incidence of this disease are urgently needed.